Qualitative characteristics of the Russian insurance market - A. N. Yampolsky (Путеводитель предпринимателя, 2020)
The development of the insurance market is based on the availability of insurance interests, trust and availability of effective demand. The ratio of these categories in Russia is the subject of the article.